Imaging of Mucosal Inflammation: Current Technological Developments, Clinical Implications, and Future Perspectives - Waldner, Maximilian J.; Rath, Timo; Schürmann, Sebastian; Bojarski, Christian; Atreya, Raja (Frontiers in Immunology, 2017)
In recent years, various technological developments markedly improved imaging of mucosal inflammation in patients with inflammatory bowel diseases. Whereas technological developments such as high-definition-, chromo- and autofluorescence-endoscopy led to a more precise and detailed assessment of mucosal inflammation during wide-field endoscopy, probe-based and stationary confocal laser microscopy enabled in vivo real-time microscopic imaging of mucosal surfaces within the gastrointestinal tract. Through the use of fluorochromes with specificity against a defined molecular target combined with endoscopic techniques that allow ultrastructural resolution, molecular imaging enables in vivo visualization of single molecules or receptors during endoscopy. Molecular imaging has therefore greatly expanded the clinical utility and applications of modern innovative endoscopy, now including not only diagnosis, surveillance, and treatment but also the prediction of individual therapeutic response. Furthermore, non-invasive imaging techniques such as computed tomography, magnetic resonance imaging, scintigraphy and ultrasound provide helpful information as supplement to invasive endoscopic procedures. In this review, we provide an overview on the current status of advanced imaging technologies for the clinical non-invasive and endoscopic evaluation of mucosal inflammation. Furthermore, the value of novel methods such as multiphoton microscopy, optoacoustics and optical coherence tomography and their possible future implementation into clinical diagnosis and evaluation of mucosal inflammation will be discussed.